Devoted to death: Santa Muerte, the skeleton saint - Chesnut, R. Andrew (Oxford University Press, 2012)
R. Andrew Chesnut offers a portrayal of Santa Muerte, a skeleton saint whose cult has attracted millions of devotees in the past 8 years. As a personification of death, the Grim Reapress has become one of the most popular and powerful saints on both the Mexican and American religious landscapes